The importance of cervical cancer screening and factors related to non-adherence (Research, Society and Development, 2021)
Objective: To identify the profile of women attended at a Basic Health Unit, the frequency of the PCCU and the factors that influence non-adherence to the exam. Methodology: Descriptive, exploratory and quantitative study, carried out in a Basic Health Unit in the center of Açailândia / MA with 140 women. A form was applied, containing variables related to the socio-demographic profile, clinical / gynecological profile and adherence to the exam. Results: It was evidenced that 64.3% of the participants are in the age group between 15 and 37 years old, 55% are brown, 57.9% have finished high school, 53.6% are married, 67.1% are in charge of household activities and 60% had no monthly income. Most (84.3%) have up to 3 children, started sexual activity between 11 and 18 years old (69.3%), had a steady partner (96.4%) and 45.7% reported not using condoms during sexual intercourse . Regarding the performance of the PCCU, 85% had already performed it, being the most frequent period of 1 year (52.9%) and, on average, 14.3% reported not performing the preventive exam as recommended due to embarrassment or lack of time. Conclusion: It is known that knowing and evaluating the profile of women attended at a BHU contributes to the knowledge of the population profile, corroborating the reduction in cervical cancer rates. Given this, investment in health education and training, both for professionals and patients, is fundamental, in addition to providing comprehensive health care, knowing the profile of the population and, thus, the greater coverage of screening, promotion programs. , prevention and health education, also including strategies for coping with the disease, thereby reducing its incidence and mortality from cervical cancer.